POLITIK HUKUM CAGAR BUDAYA DALAM PERLINDUNGAN IDENTITAS BANGSA INDONESIA - Arifin, Hafidz Putra (Faculty of Law, Parahyangan Catholic University, 2018)
The 1945 Constitution contain a ruling obligating the government to protect and preserve all cultural objects, manifestation of the nation’s culture, as cultural heritage. It is conceded that the political will as reflected in regulations made from time to time on the protection of the nation’s cultural heritage are oriented towards preservation of the Indonesian identity and furthering social welfare. In reality however, cultural heritage objects are vulnerable to looting, willful destruction or lack of care. Using a juridical normative method, the author shall examine existing rules and regulation regarding protection of cultural heritage. One important finding from this research is that low quality of cultural heritage protection is the result of low societal understanding of the importance of cultural heritage in the making of the national identity.